Genetic divergence in lentil (Lens culinaries Medik.) - Zulquarnine, SAS; Bhuiyan, MSR; Hossain, MS (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Bangladesh Journal of Plant Breeding and Genetics, Vol.22(1) June 2009 37-42